EFEKTIVITAS PENGGUNAAN LABORATORIUM BAHASA DALAM PEMBELAJARAN KETERAMPILAN MENYIMAK BAHASA JERMAN MAHASISWA PRODI PENDIDIKAN BAHASA JERMAN FBS-UNM - Usman, Misnawaty; Dalle, Ambo; Azizah, Laelah; Ernawati, Ernawati (Interference: Journal of Language, Literature, and Linguistics, 2020)
Abstract. This research is quasy experiment , two group pretest - posttest design that aims to determine the effectiveness using the language laboratory learning listening skills in German language students , German Study Program, Faculty of Language and Literature, Makassar State University. The population in this study were students on the second semester, academic year 2015, German language education students, totaling 22 people , and the sample used in this study is total sample . Hypothesis testing using t- test. Analysis using t-test, tcount = 2.42 while t tabel= 2.086 t count â‰¥ t table (2.42 â‰¥ 2.086 ) . So, H0 stating that use of the language laboratory is not effective in listening skills German student education is rejected. Consequently H1 which states that the use of effective language laboratory in the listening skills of students in the education department of the German language is accepted. The results of this study can be concluded that teaching by using a language laboratory can be used as a medium of learning to improve listening skills of students in the German language.